A study on temperature, relative humidity, and energy consumption in long-distance trains air conditioning systems in Indonesia - Fathurrahman Yudhi; Muhammad Idrus Alhamid; Nandy Putra; Arnas Lubis (Case Studies in Thermal Engineering)
Trains are efficient and cost-effective means of public transportation capable of carrying large groups of passengers. The Heating, Ventilation, and Air Conditioning (HVAC) system, a significant component with substantial energy usage in train operations, often encounters issues due to problems with the HVAC system failing to provide comfortable air quality, ultimately impacting passenger satisfaction and posing concerns for operators. A significant disparity in understanding of HVAC systems on Indonesian trains is frequently observed in tropical regions, where ensuring good air quality, stable temperatures, and controlled relative humidity levels over extended periods poses unique challenges due to the typically hot and humid climate characterized by high external temperatures and fluctuating humidity levels. Therefore, this study aimed to evaluate the ability of HVAC systems to maintain temperature and humidity in trains. Temperature and humidity were measured during the journey at various areas in passenger compartments in three executive class intercity trains, covering both day and night conditions. The results showed that maintaining a consistent level of thermal comfort parameters throughout the journey was challenging for HVAC systems. Data suggests that temperature fluctuations took place during the daytime, whereas relative humidity (R.H) levels in the night and early morning rose to 28.2 °C and 81.2 % respectively, surpassing the established standards ISO 19659–2 of 27 °C for temperature and 65 % percent for relative humidity. These results were expected to guide the improvement of future HVAC systems designs, enhancing their ability to maintain consistent temperature under varying conditions. Additionally, the designs would focus on better humidity control through the incorporation of a reheating process in air supply, ensuring consistency of long-distance journey.